A cross‐sectional survey of Australian healthcare professionals' confidence, evidence‐based knowledge and guideline use for antenatal asthma management. (18th April 2022) - Wright, Thomas K.; McLaughlin, Karen; Jensen, Megan E.; Robijn, Annelies L.; Foureur, Maralyn; Murphy, Vanessa E.
Abstract : Background: Asthma is one of the most common chronic health conditions experienced during pregnancy and is associated with numerous adverse maternal and perinatal outcomes. Aims: To better understand the confidence, evidence‐based knowledge and guideline use among healthcare professionals around Australia commonly involved in providing antenatal care for women with asthma. Materials and Methods: An online, cross‐sectional survey was developed and distributed to maternity carers (obstetricians and midwives), primary carers (general practitioners and general practice nurses) and respiratory specialists (respiratory physicians and respiratory nurses). Self‐reported confidence and use of clinical guidelines were recorded. Evidence‐based knowledge was assessed with 13 questions relating to four clinical scenarios that covered recommendations from national and international guidelines. Results: Primary carers and respiratory specialists were more confident in providing antenatal asthma care, more likely to use clinical guidelines and scored significantly higher in evidence‐based knowledge of antenatal asthma management than maternity carers ( P < 0.01 and P < 0.001, respectively). There was no significant difference in evidence‐based knowledge among healthcare professionals from metropolitan, regional and rural backgrounds. However, healthcare professionals who used clinical guidelines scored significantly higher than those who did not ( P < 0.0001). Conclusion: Greater utilisation of clinical guidelines could improve the evidence‐based knowledge of maternity carers. However, the absence of antenatal asthma management in obstetric‐ and maternity‐specific guidelines poses a potential barrier that needs to be addressed. Furthermore, the development of multidisciplinary antenatal clinics, staffed by respiratory nurses and/or physicians, could improve outcomes for pregnant women with asthma who are not undertaking shared care.